How the Nursing Practice Environment Influences Retention and Turnover Intention: An Umbrella Review Protocol - Figueiredo, Ana Rita (2024)
Currently, there is a global shortage of nurses, which has a negative impact on health institutions, mainly on the quality of care provided. The quality of nursing care depends on several factors, including the nursing practice environment, which has been stated as a fundamental element for the successful functioning of health systems. Scientific evidence shows that favorable practice environments contribute to nurse retention, and unfavorable environments increase nurses’ turnover intention. Retaining nurses is essential to ensure the sustainability of healthcare organizations and the quality of nurse care. In the current shortage scenario, this issue has become even more significant. Objective: This review aims to identify systematic literature reviews that describe the characteristics of nursing practice environments that contribute to nurse retention or turnover intention in hospitals. Methods: The umbrella review will follow the Joanna Briggs Institute methodology, the Preferred Reporting Items for Systematic Review and Meta-Analysis reporting guidelines, and the Preferred Reporting Items for Overviews of Reviews guidelines. A search with indexed terms will be performed in various databases, and two reviewers will identify, select, and extract studies, while a third reviewer will resolve any disagreements. Results: This protocol provides a structured approach for conducting the review, and the initial searches have identified 440 articles, with no previous protocol or umbrella review identified, underscoring the importance of this research. Conclusions: This study will enhance the dissemination of scientific evidence regarding nursing practice environments, thereby contributing to an improved understanding of factors affecting nurse retention and turnover intention.